Preparation method of multicolor luminous zinc-based halide organic-inorganic hybrid glass

By developing multi-color luminescent zinc-based halide organic-inorganic hybrid glass, the problem of failure of organic-inorganic metal halide materials in the prior art to achieve a successful transformation to amorphous phase glass is solved, and the development of efficient, transparent and economical luminescent glass materials has been achieved, which has improved the performance and reliability of LED and X-ray imaging technologies.

CN119613452APending Publication Date: 2025-03-14WENZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792629.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-03-14

Smart Images

  • Figure CN119613452A_ABST
    Figure CN119613452A_ABST
Patent Text Reader

Abstract

The invention discloses multicolor luminous zinc-based halide organic-inorganic hybrid glass and a preparation method thereof. The matrix component of the halide glass is A2Zn1-xBr4, A represents a triphenylphosphonium organic molecule, active ions are one or two of xMn < 2 + > or xSb < 3 + >, x is greater than or equal to 0.3 and less than or equal to 0.9, and the glass is transparent light yellow under natural light. The single-doped Mn < 2 + > and Sb < 3 + > halides respectively emit broadband green light and red light to a near-infrared region under the irradiation of ultraviolet light, and the co-doped glass can emit characteristic light of two ions. The preparation method is as follows: triphenylphosphonium bromide and metal bromide are used as raw materials, CH2Cl2 is used as a solvent, Et2O is used as an anti-solvent, and the transparent crystal is synthesized through a diffusion method. And heating the crystal in air to a molten state, carrying out the whole process in the air, and slowly cooling to room temperature to obtain the multicolor luminous halide glass which can be used for X-ray imaging and near-infrared LEDs (Light Emitting Diodes).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multicolor luminescent glass material, and in particular to a transparent luminescent crystal emitting green light, red light and infrared light, and a process flow of converting the crystal into glass at a temperature as low as 190°C. The present invention specifically relates to a glass material capable of absorbing light of 200 to 500 nm and 300 to 500 nm, respectively, and having emission peaks between 450 to 650 nm and 550 to 800 nm, respectively, and can be applied to near-ultraviolet semiconductor LEDs (night vision devices) and X-ray imaging fields. Background Art

[0002] Transparent luminescent glass has unique applications in optoelectronic fields such as three-dimensional optical data storage and multi-level encryption, LED transparent screens, etc., which has aroused the research interest of researchers. In the past, a large number of literatures have reported transparent luminescent glass, but most of them focus on oxide rare earth luminescent glass, such as Pr 3+ , Tb 3+ 、Eu 3+ The luminescent glass doped with rare earth ions absorbs wavelengths in the ultraviolet region (the absorption band is narrow) [Adv.Optical Mater., 2024, 2401648; Ceram.Inter., 2019, 45, 4108-4112; J.Alloy.Comp., 2019, 806, 1410-1418] and cannot be used for LEDs. At the same time, harsh synthesis conditions such as melting temperatures above 1000°C and expensive raw material costs limit their large-scale production in the market. In recent years, organic-inorganic hybrid luminescent glass has shown great development potential in applications such as three-dimensional optical storage, rewritable photo patterns, and multi-mode anti-counterfeiting due to its advantages such as high carrier mobility, low trap state density, high photoluminescence quantum efficiency, and low-cost solution processability [J.Am.Chem.Soc.2024, 146, 7373-7385].

[0003] Compared with luminescent glass, traditional phosphors need to go through a complex process in LED applications, including mixing with glue, epoxy resin encapsulation and other steps. The particle size of the phosphor is uneven, the agglomeration is serious, and the texture is hard, which requires tedious pre-treatment such as powder picking, crushing, and screening, and the mixing ratio of phosphor and glue also needs to be precisely controlled. In addition, the service life of LEDs is significantly affected by organic matter such as epoxy resin. In X-ray imaging, the preparation of thin films is also crucial, which involves the proportion of organic solvents, phosphors, and high-mold solutes. Therefore, the development of organic-inorganic hybrid luminescent glass that does not require additional processing to replace phosphors is of great significance to the improvement of LED and X-ray imaging technology.

[0004] Although a large number of literatures have reported on organic-inorganic metal halide crystals, most of the research has focused on crystal synthesis and luminescence properties, and has failed to achieve the transition from crystals to luminescent glass. [Laser Photonics Rev. 2024, 2400244, Angew. Chem. Int. Ed. 2024, 63, e202402634]. This shows that in order to meet the needs of LED and X-ray imaging, further research and development of suitable organic-inorganic metal halide materials is needed to achieve their successful transition to amorphous phase glass, thereby overcoming the limitations of existing phosphor materials and improving the performance and reliability of related optoelectronic devices. Summary of the invention

[0005] In the fields of lighting and X-ray imaging, the development of efficient, transparent and affordable luminescent glass materials is crucial.

[0006] The present invention discloses a multi-color luminescent zinc-based halide organic-inorganic hybrid glass and its preparation method. The chemical formula of this breakthrough invention is A2Zn 1-x Br4:xMn 2+ and A2Zn 1-x Br4:xSb 3+ , where A represents an organic molecule allyltriphenylphosphonium (C 21 H 20 P), phenethyl triphenylphosphonium (C 26 H 26 P), propyltriphenylphosphonium (C 21 H 22 P) and benzyltriphenylphosphonium (C 25 H 26 P) one or more; A2Zn 1-x Br4:xMn 2+ and A2Zn 1-y Br4:ySb 3+ Halide glass is light yellow and transparent under natural light, and emits broadband green and red light under ultraviolet light, and the red light involves the near-infrared region. 2+ and Sb 3 + Halide glass is light yellow and transparent under natural light, and emits green, red and near-infrared light under ultraviolet light.

[0007] The excitation spectrum of the present invention is in the range of 200-500nm and 300-500nm respectively. The excitation and emission of green glass are both derived from Mn 2+ dd transition, that is, under ultraviolet light, Mn 2+The photon of the present invention is transferred from the ground state to the excited state of the high energy level, and then the broadband green light is emitted when the photon returns to the ground state. 3+ sp transition, that is, under the irradiation of this light, Sb 3+ The photon jumps from the ground state to the high-energy excited state, and when it returns to the ground state, it emits red light to the infrared broadband.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing multicolor luminescent zinc-based halide organic-inorganic hybrid glass: A2Zn 1-x Br4:xMn 2+ and A2Zn 1- y Br4:ySb 3+ The raw materials used in the preparation of the halide include triphenylphosphonium bromide, ZnBr2 (99.9%), MnBr2 (99.9%), SbBr3 (99.9%), CH2Cl2 (99.9%), and Et2O (99.9%), all of which can be purchased on the market. Organic bromide and metal bromide are mixed in a stoichiometric ratio and dissolved in 4mL CH2Cl2. Et2O is diffused into the above solution for 0.5-2 days at room temperature to generate organic-inorganic hybrid transparent crystals through the anti-solvent effect. The obtained crystals are then heated to a molten state at a specific temperature, the whole process is carried out in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide transparent glass.

[0010] The organic molecule of the present invention is further configured to be allyltriphenylphosphonium (C 21 H 20 P), phenethyl triphenylphosphonium (C 26 H 26 P), propyltriphenylphosphonium (C 21 H 22 P) and benzyltriphenylphosphonium (C 25 H 26 P) One or both.

[0011] The doping concentration of the present invention is further set to 0.2≤x≤0.8.

[0012] The heating temperature of the present invention to the molten state is further set to 140-180°C.

[0013] The present invention is further provided with a melting heating time of 0.5 to 1.5 hours.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0015] 1) Compared with commercial oxide glass, the raw materials used in the present invention are cheap and readily available, and the entire preparation process can be carried out in the air without the need for a special environment, thereby reducing costs.

[0016] 2) The excitation spectrum of the present invention is located in the near-ultraviolet region of 300 to 500 nm, and is expected to be applied to ultraviolet LEDs.

[0017] 3) Compared with traditional silicate luminescent glass, the melting temperature of the present invention is significantly reduced to 130-190°C, which is much lower than the 1300°C or more of traditional silicate glass, which reduces the requirements for equipment and is conducive to industrial production.

[0018] 4) The uniqueness of the present invention lies in the realization of the transformation from organic-inorganic hybrid halide crystals to glass. This innovation has brought an important breakthrough for glass lighting materials.

[0019] Through these advantages, the present invention not only shows innovation in preparation technology, but also meets the high standard requirements in the field of LED and X-ray imaging in terms of performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions and product performance in the embodiments, the following drawings are used for illustration.

[0021] Figure 1 The glass material (C) prepared in Examples 1 and 2 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ (Left), (C 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ (Right) Photograph taken under visible light.

[0022] Figure 2 The glass material (C) prepared in Examples 1 and 2 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ , (C 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ XRD pattern of .

[0023] Figure 3 The glass material (C) prepared in Example 1 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ Excitation and emission spectra.

[0024] Figure 4 The glass material (C) prepared in Example 2 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ Excitation and emission spectra. Specific implementation methods

[0026] In order to better explain the present invention, the present invention is further described below in conjunction with embodiments and drawings for a better understanding of the present invention. However, the scope of protection claimed in the present invention is not limited to the scope represented by the embodiments.

[0027] Example 1

[0028] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.7mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.3mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution at room temperature for 1 day to generate organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ The crystals are heated at 180°C for 1.5 hours until they are molten, all in air, and then slowly cooled to room temperature to obtain an organic-inorganic hybrid halide green glass. Figure 1 The glass shown on the left is transparent light yellow. The product phase was detected by XRD powder diffractometer (Bruker D8Advance) at room temperature. Figure 2 As shown, XRD characterization shows that the crystal synthesized by the present invention is pure phase (C 21 H 20 P)2Zn 0.7 Br4 material. The luminescence properties were studied using a Fluoromax-4 fluorescence spectrometer (HORIBA Jobin Yvon Inc.). Figure 3 As shown, (C 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ The excitation spectrum of the glass is in the range of 200-500nm, and it emits bright green light of 520nm under ultraviolet light. 2+ Partially replace Zn 2+ Produces fluorescence.

[0029] Example 2

[0030] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.7mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.3mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1.5 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ The crystals are heated at 180°C for 1.5 hours until they are molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. Figure 1 The glass shown on the right is transparent light yellow. Figure 2 As shown, XRD characterization shows that the crystal synthesized by the present invention is pure phase (C 21 H 20 P)2Zn 0.7 Br4 material. Figure 4 As shown, (C 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ The excitation spectrum of the glass is in the range of 300-500nm, and it emits bright red light of 654nm under ultraviolet light. 3+ Partially replace Zn 2+ Produces fluorescence.

[0031] Example 3

[0032] A method for preparing organic-inorganic hybrid halide yellow glass under ultraviolet light irradiation: accurately weighing 0.6mmol ZnBr2, 2mmol C 21 H 20 PBr, 0.1mmol MnBr2 and 0.3mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.7 Br4:0.1Mn 2+ , 0.3Sb 3+The crystals were heated at 170°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain an organic-inorganic hybrid halide yellow glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0033] Example 4

[0034] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.5mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.5 Br4:0.5Mn 2+ The crystals were heated at 160°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0035] Example 5

[0036] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.7mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.3mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution at room temperature for 1 day to generate organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.7 Br4:0.3Mn 2+ The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0037] Example 6

[0038] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H20 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution at room temperature for 1 day to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to obtain transparent crystals. Then (C 21 H 20 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0039] Example 7

[0040] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 0.5 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 160°C for 0.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0041] Example 8

[0042] A method for preparing organic-inorganic hybrid halide green light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution at room temperature for 1 day to generate organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to obtain transparent crystals. Then (C 21 H 20 P)2Zn 0.2 Br4:0.8Mn 2+The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0043] Example 9

[0044] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.7mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.3mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 0.5 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.7 Br4:0.3Sb 3+ The crystals were heated at 160°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0045] Example 10

[0046] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.8mmol SbBr3 (0.8mmol) were dissolved in 4mL dichloromethane, and ether was diffused into the above solution at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 140°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0047] Embodiment 11

[0048] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21H 20 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 150°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0049] Example 12

[0050] A method for preparing an organic-inorganic hybrid halide orange light glass under ultraviolet light irradiation: accurately weighing 0.5 mmol ZnBr2, 2 mmol C 21 H 20 PBr, 0.1mmol MnBr2 and 0.4mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.5 Br4:0.1Mn 2+ ,0.4Sb 3+ The crystals were heated at 160°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain an organic-inorganic hybrid halide orange glass. The product glowed red under ultraviolet light, and its appearance and XRD were similar to those of Example 2. Mn appeared in the fluorescence spectrum. 2+ With Sb 3+ Typical emission bands.

[0051] Embodiment 13

[0052] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H20 P)2Zn 0.5 Br4:0.5Sb 3+ The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0053] Embodiment 14

[0054] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 21 H 20 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.5 Br4:0.5Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0055] Embodiment 15

[0056] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 20 P)2Zn 0.5 Br4:0.5Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0057] Example 16

[0058] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.5 Br4:0.5Sb 3+ The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0059] Embodiment 17

[0060] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.5mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 0.5 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.5 Br4:0.5Mn 2+ The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0061] Embodiment 18

[0062] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22P)2Zn 0.5 Br4:0.5Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0063] Embodiment 19

[0064] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.5mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.5 Br4:0.5Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0065] Embodiment 20

[0066] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.3mmol ZnBr2, 2mmol C 25 H 26 PBr and 0.7mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 25 H 26 P)2Zn 0.3 Br4:0.7Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0067] Embodiment 21

[0068] A method for preparing an organic-inorganic hybrid halide orange light glass under ultraviolet light irradiation: accurately weighing 0.5 mmol ZnBr2, 2 mmol C 21 H 22 PBr, 0.1mmol MnBr2 and 0.4mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.5 Br4:0.1Mn 2+ ,0.4Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain an organic-inorganic hybrid halide orange light glass. The product emitted orange light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0069] Embodiment 22

[0070] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.8mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.8 Br4:0.2Sb 3+ The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0071] Embodiment 23

[0072] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.7mmol ZnBr2, 2mmol C 26 H 26PBr and 0.5mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.7 Br4:0.3Sb 3+ The crystals were heated at 160°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0073] Embodiment 24

[0074] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.6mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.4 Br4:0.6Sb 3+ The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0075] Embodiment 25

[0076] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.8mmol ZnBr2, 2mmol C 26 H 26 PBr and 0.5mmol SbBr3 (0.2mmol) were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 26 H 26 P)2Zn 0.8 Br4:0.2Sb 3+The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0077] Embodiment 26

[0078] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.6mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.4 Br4:0.6Sb 3+ The crystals were heated at 120°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0079] Embodiment 27

[0080] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.3mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.7mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.3 Br4:0.7Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0081] Embodiment 28

[0082] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0083] Embodiment 29

[0084] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 160°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0085] Embodiment 30

[0086] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0087] Embodiment 31

[0088] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 130°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0089] Embodiment 32

[0090] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.6mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.4 Br4:0.6Sb 3+ The crystals are heated at 140° C. for 1 hour until they are in a molten state, the entire process being carried out in air, and slowly cooled to room temperature to obtain an organic-inorganic hybrid halide red light glass.

[0091] Embodiment 33

[0092] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.3mmol ZnBr2, 2mmol C 21 H 22PBr and 0.7mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.3 Br4:0.7Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0093] Embodiment 34

[0094] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 140°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0095] Embodiment 35

[0096] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+The crystals were heated at 150°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0097] Embodiment 36

[0098] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 140°C for 0.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0099] Embodiment 37

[0100] A method for preparing organic-inorganic hybrid halide red light glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol SbBr3 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 1 day at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Sb 3+ The crystals were heated at 140°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide red glass. The product glowed red under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 2.

[0101] Embodiment 38

[0102] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 21 H22 PBr and 0.6mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.4 Br4:0.6Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0103] Embodiment 39

[0104] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.3mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.7mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.3 Br4:0.7Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0105] Embodiment 40

[0106] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Mn 2+The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0107] Embodiment 41

[0108] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0109] Embodiment 42

[0110] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 160°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0111] Embodiment 43

[0112] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.3mmol ZnBr2, 2mmol C 21 H22 PBr and 0.7mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.3 Br4:0.7Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0113] Embodiment 44

[0114] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.5mmol ZnBr2, 2mmol C 25 H 26 PBr and 0.5mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 25 H 26 P)2Zn 0.5 Br4:0.5Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0115] Embodiment 45

[0116] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.7mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.4 Br4:0.7Mn 2+The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0117] Embodiment 46

[0118] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 25 H 26 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 25 H 26 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 130°C for 2 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0119] Embodiment 47

[0120] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.4mmol ZnBr2, 2mmol C 21 H 22 PBr and 0.7mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 21 H 22 P)2Zn 0.4 Br4:0.7Mn 2+ The crystals were heated at 160°C for 1.5 hours until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0121] Embodiment 48

[0122] A method for preparing organic-inorganic hybrid halide chlorine glass under ultraviolet light irradiation: accurately weigh 0.2mmol ZnBr2, 2mmol C 25 H26 PBr and 0.8mmol MnBr2 were dissolved in 4mL CH2Cl2, and Et2O was diffused into the above solution for 2 days at room temperature to form organic-inorganic hybrid crystals. Subsequently, the crystals were washed three times with ethanol and dried at 60℃ for 5 hours to form transparent crystals. Then (C 25 H 26 P)2Zn 0.2 Br4:0.8Mn 2+ The crystals were heated at 150°C for 1 hour until they were molten, all in air, and slowly cooled to room temperature to obtain organic-inorganic hybrid halide green glass. The product emitted green light under ultraviolet light, and its appearance, XRD, and fluorescence spectrum were similar to those of Example 1.

[0123] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A multicolor luminescent zinc-based halide organic-inorganic hybrid glass, characterized in that: The chemical formula of this halide green and red glass is A2Zn 1-x Br4:xMn 2+ and A2Zn 1-x Br4:xSb 3+ , where A represents an organic molecule allyltriphenylphosphonium (C 21 H 20 P), phenethyl triphenylphosphonium (C 26 H 26 P), propyltriphenylphosphonium (C 21 H 22 P) and benzyltriphenylphosphonium (C 25 H 26 P) one or more, single doping Mn 2+ and Sb 3+ Under ultraviolet light, the halides emit broadband green light, red light to the near-infrared region, and the co-doped Mn 2+ and Sb 3+ The glass can emit the characteristic light of two ions at the same time, namely green light, red light to near-infrared light.

2. The multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 1, characterized in that: 0.1≤x≤0.9, that is, Mn 2+ or Sb 3+ The doping concentration is Zn 2+ 10%-90%.

3. The method for preparing a multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 1, characterized in that: Triphenylphosphonium bromide, ZnBr2 and MnBr2 (or SbBr3) are accurately weighed and placed in a glass bottle according to a stoichiometric ratio and dissolved in CH2Cl2. The open glass bottle is placed in an Et2O solution, and Et2O is diffused in the glass bottle at room temperature to precipitate organic-inorganic hybrid crystals in the solution of the glass bottle. The organic-inorganic hybrid crystals are then heated to a molten state, the whole process is carried out in air, and slowly cooled to room temperature to obtain an organic-inorganic hybrid halide glass.

4. The method for preparing a multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 3, characterized in that: The ratio of triphenylphosphonium bromide, ZnBr2 and MnBr2 (or SbBr3) is 2:0.1-0.9:0.9-0.

1.

5. The method for preparing a multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 3, characterized in that: The diffusion antisolvent is Et2O, the temperature is at room temperature, and the diffusion time is 0.5-2 days.

6. The method for preparing a multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 3, characterized in that: The heating temperature of the crystals to the molten state is 130-190°C.

7. The method for preparing a multicolor luminescent zinc-based halide organic-inorganic hybrid glass according to claim 3, characterized in that: The heating time of the crystals to the molten state is 0.5-2 hours.